Conflict Management in Health Care of Cassandra’s Schizophrenia According Torey Hayden’s Twilight Children - Agus Setiawan, Yudi (J-LEE - Journal of Law, English, and Economics, 2023)
The conflict is a disagreement within oneself or differences or dispute among persons that has potential to cause harm. The research is aimed to analyze the symptoms of schizophrenia which appear in a character named Cassandra, and Cassandra’s ways to overcome her schizophrenia in the novel Twilight Children by Torey Hayden. In this research, descriptive qualitative method is used to analyze the data; the novel by Torey Hayden with the tittle Twilight Children. The data source of this study was the novel which is analyzed by using psychoanalysis. There are steps done in analyzing the novel. The first is determining the novel which is going to be analyzed that is the novel Twilight Children and the second is obtaining the elements of the novels, such the narrations, utterances, attitudes and the characterization of Cassandra. It is done to analyze them dealing with the research question about the symptoms of schizophrenia in the main character, and the ways to overcome those symptoms. The third is analyzing the data by connecting them with the psychoanalysis theory, especially theory about basic anxiety by Karen Horney and theory about schizophrenia and the treatments to recover from schizophrenia. There are four main symptoms of schizophrenia found in the main character Cassandra, the development of basic anxiety is the most triggering factor which causes those symptoms appear.